“The Legality of Prisoner of War Labour in England, 1648–1655” - Tycko, S (Oxford University Press, 2020)
Prisoners of war formed a legally distinct category amongst the many thousands of people forcibly employed in England and the English American colonies in the mid-seventeenth century, but they have yet to be studied as such. Focusing on 1648 to 1655, this article explains how a succession of English governments sent their war captives into servitude with private masters despite the prohibition of hard labour for Christian prisoners in the customary laws of war. They instead operated under the logic of the English poor law, in which the indigent could meaningfully consent to serve a master even while under duress. The case of Scottish and Dutch prisoners of war in the Bedford Level fen drainage project shows how the Council of State and the drainage company board members conceptualized common prisoners as willing workmen. Prisoners, ambassadors, and a variety of English observers instead thought that war captives should not have to work for their subsistence or their captors’ profit. Nevertheless, common prisoners continued to labour under the aegis of free contracts into the eighteenth century.